Acceptability of virtual therapy for postpartum women during COVID-19: A national mixed methods study - Gonzalez, Carmen; Ramirez, Magaly; Mata-Greve, Felicia; Diaz, Autumn; Duran, Miriana C.; Johnson, Morgan; Grote, Nancy; Areán, Patricia A. (Frontiers in Psychiatry, 2022)
Background Postpartum depression (PPD) affects one in eight women in the U.S., with rates increasing due to the COVID-19 pandemic. Given the unique circumstances of COVID-19, virtual therapy might be a unique way to overcome barriers to mental health services. The study sought to explore the acceptability of virtual therapy among women in the postpartum period. Methods Using an online recruitment mixed methods approach, we collected data from a U.S. national cross-sectional sample of women (N = 479) who gave birth in the last 12 months. Findings Results show that 66% of women endorsed items consistent with possible depression during the COVID-19 pandemic. Only 27% accessed therapy services during the postpartum period. While 88% were open to engaging in virtual therapy services, 12% identified several major concerns with virtual therapy, namely: (1) preference for in-person therapy (2) no perceived need for therapy (3) uncomfortable with virtual therapy, and (4) lack of privacy. Of note, 36% more Latinas reported dissatisfaction with quality of care received during virtual therapy compared to non-Latina participants. Despite a major shift to virtual care with COVID-19, future work is needed to make virtual mental health services more accessible for women with PPD.